A woman's Attitudes Toward Her Body In The Age Of CosmeticsA field Study On A Sample Of Female Students At The Faculty Of Medicine At Damascus University (Damascus University Journal of arts and humanities sciences, 2025)
The research aims to know the woman’s view of her body in the era of beauty, and the extent of the influence of society in her view of her own body and her resort to plastic surgery, among a sample of female students (18-30) at the University of Damascus: Faculty of Medicine. The data included the sample (200) female students.The research reached a number of basic results, foremost of which came the presence of a statistically significant effect of society’s view of a woman’s body on a woman’s view of her own body. There is also a statistically significant effect of the society’s view of the woman’s body in resorting to plastic surgery. The results of the study also showed that there is a statistically significant effect of a woman’s view of her body in resorting toplastic surgery. The results of the study also showed that there is a statistically significant effect between the feeling of self-satisfaction with the woman's view of her body and the resort to plastic surgery, in addition to the existence of a statistically significant relationship between the feeling of others' satisfaction with the woman's view of her body and the resort to plastic surgery.
Keywords: women; beauty; body; Age of cosmetics; Satisfaction; Undergraduate